2014
DOI: 10.1002/jhet.1823
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of New Thieno[2,3‐d]pyrimidin‐4(3H)‐one Derivatives for Evaluation as Anticancer Agents

Abstract: Thieno[2,3‐d]pyrimidinones were reported to act as potent anticancer agents; in this work, a series of new substituted thieno[2,3‐d]pyrimidinone (6) were synthesized via the aza‐Wittig reaction in satisfactory yields. The structures of these compounds were confirmed by elemental analysis, IR, 1H‐NMR, and mass spectral data, and compound 6h was further analyzed by single crystal X‐ray diffraction. Cytotoxic effect of all the compounds was carried out on human breast and lung cancer cell lines (MCF‐7 and SPC‐A‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Following the usual methods, 24 treatment of commercially available ethyl 2-amino-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylate (1) with 4,5-dichloro-1,2,3-dithiazolium chloride (Appel's salt) (2) in dichloromethane at room temperature afforded 68% of the corresponding iminodithiazole (3) (Scheme 3). The presence of the fused cyclohexane ring avoids unwanted addition of Appel's salt at position C-5 of the thiophene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the usual methods, 24 treatment of commercially available ethyl 2-amino-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carboxylate (1) with 4,5-dichloro-1,2,3-dithiazolium chloride (Appel's salt) (2) in dichloromethane at room temperature afforded 68% of the corresponding iminodithiazole (3) (Scheme 3). The presence of the fused cyclohexane ring avoids unwanted addition of Appel's salt at position C-5 of the thiophene.…”
Section: Resultsmentioning
confidence: 99%
“…We found that standard methods at room temperature 24 applied to the preparation of 2-Niminodithiazolothiophene derivatives led to a complex mixture of polymeric oily compounds resulting from electrophilic substitution at C-5 of the thiophene ring by N-1 of Appel's salt (2). Nevertheless, condensation of the starting amino ester (8) with one equivalent of Appel's salt (2) in dichloromethane at low temperature (-20 °C) followed by addition of pyridine (2 equiv.)…”
Section: Scheme 4 Synthesis Of the Novel Pentacyclic Thieno[23-d]pymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have focused on the synthesis of nitrogenous heterocyclic compounds via aza-Wittig reaction, attempting to apply and evaluate their biological activities ( Hu et al, 2010 ; Hu et al, 2014 ; Wang et al, 2016a ; Wang et al, 2016b ; Li et al, 2016 ; Liu M.-G. et al, 2019 ; Liu N. et al, 2019 ; Gao et al, 2019 ; Liu et al, 2021 ). Herein, we designed a Schiff base bearing furopyrimidinone scaffold ( FPS ) synthesized from 2-hydroxy-benzaldehyde with furo [2,3-d]-pyrimidine-5-carbohydrazide ( Scheme 1 ), and fluorescence analysis showed that FPS displayed highly selective recognition Zn 2+ with no apparent interference from other metal ions in MeOH solution and its applications in cell imaging and detection Cu 2+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation for the preparation of thieno[2,3-d]pyrimidin-4(3 H )-ones has intrigued researchers to make numerous efforts in synthetic methodology [21,22,23,24,25]. In the course of searching for new cholinesterase inhibitors based on evodiamine, we reported a new one-pot protocol for the straightforward synthesis of rutaecarpine and its analogs from isatoic anhydride and 4,9-dihydro-3 H -pyrido[3,4- b ]indole [26,27].…”
Section: Introductionmentioning
confidence: 99%